2015
DOI: 10.1001/jama.2014.15770
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance by Medical Students Working Individually or in Teams

Abstract: Diagnostic errors contribute substantially to preventable medical error. 1 Cognitive error is among the leading causes and mostly results from faulty data synthesis. 2 Furthermore, reflecting on their confidence does not prevent physicians from committing diagnostic errors. 1 Diagnostic decisions usually are not made by individual physicians working alone. Our aim was to investigate the effect of working in pairs as opposed to alone on diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 4 publications
7
81
0
Order By: Relevance
“…This result can be considered in agreement with several studies on different medical issues showing that predictor's confidence correlates very well with the correctness of the prediction ( Detsky et al , 2017; Hautz et al , 2015; Kämmer et al , 2017; Kurvers et al , 2016). Indeed, the concordance of different members of a given group (students or runs of the random forest model) can be taken as indicating that the agent is "sure" of the forecast.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result can be considered in agreement with several studies on different medical issues showing that predictor's confidence correlates very well with the correctness of the prediction ( Detsky et al , 2017; Hautz et al , 2015; Kämmer et al , 2017; Kurvers et al , 2016). Indeed, the concordance of different members of a given group (students or runs of the random forest model) can be taken as indicating that the agent is "sure" of the forecast.…”
Section: Discussionsupporting
confidence: 92%
“…However, when expert people are involved, even small groups can outperform the best among them, at least when a yes/no answer to well-defined diagnostic questions is requested based on radiographic/ histological images, ( Kurvers et al , 2016; Sonabend et al , 2017; Wolf et al , 2015). Studies with medical students show that working in pairs ameliorates diagnostic ability, with further improvements when group size increases ( Hautz et al , 2015; Kämmer et al , 2017), in line with the core idea of Collective intelligence.…”
Section: Introductionmentioning
confidence: 66%
“…8,9,10,11 To date, the existing evidence on the role of collective intelligence in general clinical diagnosis has been limited to single-center studies of medical students. 11,16 However, in most medical specialties, the diagnostic process requires combining many pieces of information while considering multiple diagnoses. The present study focused on general clinical diagnosis rather than binary decisions in narrow medical domains and, to our knowledge, is the largest study to date of collective intelligence in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the frequency of diagnostic errors is thus a major step toward improving health care (24,25). Previous research on collective intelligence in medical diagnostics has yielded conflicting results: Some studies have found that group decision making boosts diagnostic accuracy (9,12,26,27), whereas others have found null or even detrimental effects (28,29).…”
mentioning
confidence: 99%